Waves of War : Nationalism, State Formation, and Ethnic Exclusion in the Modern World / [electronic resource] - Wimmer, Andreas (Cambridge : Cambridge University Press, 2012)
Why did the nation-state emerge and proliferate across the globe? How is this process related to the wars fought in the modern era? Analyzing datasets that cover the entire world over long stretches of time, Andreas Wimmer focuses on changing configurations of power and legitimacy to answer these questions. The nationalist ideal of self-rule gradually diffused over the world and delegitimized empire after empire. Nationalists created nation-states wherever the power configuration favored them, often at the end of prolonged wars of secession. The elites of many of these new states were institutionally too weak for nation-building and favored their own ethnic communities. Ethnic rebels challenged such exclusionary power structures in violation of the principles of self-rule, and neighboring governments sometimes intervened into these struggles over the state. Waves of War demonstrates why nation-state formation and ethnic politics are crucial to understand the civil and international wars of the past 200 years.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).